The formation of a one-dimensional van der Waals selenium crystal from the three-dimensional amorphous phase: A spectroscopic signature of van der Waals bonding - Krbal, Miloš; Kolobov, Alexander V; Fons, Paul; Saito, Yuta; Belev, George; Kasap, Safa (American Institute of Physics, 2022)
Trigonal selenium is a prototypical one-dimensional (1D) van der Waals (vdW) solid, where covalently bonded helical chains are held together by weaker vdW forces. In this work, we have studied structural transformation from a three-dimensional amorphous phase of non-interacting Se chains into a 1D vdW crystal using x-ray absorption spectroscopy. The crystallization process and establishment of vdW interaction are accompanied by elongation and weakening of covalent Se-Se bonds. We have found a unique signature in the x-ray absorption near-edge structure spectrum that is associated with vdW bonds and can be used to identify the formation of the latter. We believe that a similar approach can be used to study other 1D vdW solids, such as transition-metal trichalcogenides, and particularly stress the usefulness of x-ray absorption spectroscopy to identify vdW bonds.
Tvorba jednorozměrného van der Waalsova krystalu selenu z trojrozměrné amorfní fáze: Spektroskopický podpis van der Waalsovy vazby
Keywords: negative correlation-energy; valence-alternation; photocrystallization; crystallization; states; selen; RTG absorpční spektroskopie; van der Waalsova vazba; jednodimenzionální; krystalizace